Obese Children with Metabolic Syndrome Have 3 Times Higher Risk to Have Nonalcoholic Fatty Liver Disease Compared with Those without Metabolic Syndrome - Dimitrios Papandreou; Mirey Karavetian; Zacharoula Karabouta; Eleni Andreou (International Journal of Endocrinology)
Background. The aim of this study was to investigate the relationship between metabolic syndrome (MS) and nonalcoholic fatty liver disease (NAFLD) in obese children. One hundred and twenty-five subjects aged 11-12 years old participated in the study. Methods. Anthropometric and biochemical indices were measured, including lipid and liver profile, blood glucose, serum insulin, and liver ultrasound. Results. Forty-four children (58.6%) were found to have MS. Insulin resistance was present in 78 (62.4%) children. Patients with MS were more likely to have NAFLD (P<0.001). Children with NAFLD had significantly higher body mass index, waist circumference, triglycerides, fasting insulin, and lower high-density lipoprotein compared to patients with normal livers (P<0.001). Insulin resistance was significantly higher in children with NAFLD (P<0.001). Obese children presenting with MS were 3.01 (2.87–3.57, P<0.002) times more likely to develop NAFLD compared to those without metabolic syndrome after adjustment of cofounders. Conclusions. Obese children with MS have a higher risk of developing NAFLD. Weight management and early prevention should be the first line of treatment to prevent any possible health issues later on.